Praktik Bagi Hasil Maw’ah Blang di Desa Alue Keurinyai dalam Perspektif Islam - Badriah; Zulfiani; Husni; Khairil Fata; Munawar Rizki Jailani; Lia Safrina (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This study aims to see how the practice of profit-sharing maw'ah blang in the agricultural sector in Alue Keurinyai village is from an Islamic perspective. This study is a qualitative study with a field study approach. Data collection was carried out through interviews and documentation. The results of the study showed that: 1) in carrying out the practice of maw'ah blang, the contract was carried out verbally, and the most frequently used cooperation system is muzara'ah, which is a collaboration between landowners and cultivators where the seeds come from the landowner with a profit sharing agreement according to mutual agreement. The profit-sharing system is carried out in two ways—first, 1/3:2/3 with 1/3 for the cultivator and 2/3 for the landowner. Second, 50%:50% using after getting the harvest, it is reduced by the initial capital, after getting the net results, it is divided 50%:50%. 2) If seen from the practices carried out by the Alue Keurinyai village community in general, it is by the theory of muzara'ah and mukhabarah discussed in the books of fiqh, while the method of profit sharing that they practice is in two forms. The first form is by the theory of muzara'ah or mukhabarah, while the second form is not in accordance, because profit sharing is carried out after deducting the initial capital, so that if the harvest does not meet the target, one of the parties will be harmed. This research is limited to the land maw'ah and in the village of Alue Keurinyai. Subsequent researchers can conduct it on other assets and in different places.